Does urban particulate matter hinder COVID-19 transmission rate? - Josep Penuelas; Marcos Fernández-Martínez; Sandra Cobo; Llorenç Badiella; Jordi Sardans (Air Quality, Atmosphere & Health, 2024)
The COVID-19 pandemic has had a significant impact on global health, with millions of people affected by the disease. Recent studies have shown that environmental factors such as air quality, temperature, and humidity can impact the survival and transmission of the virus, leading to differences in the rate of spread and severity of the disease in different regions. In this global cross-sectional study, we analyzed the relationship between environmental factors and the transmission and survival of the virus in 167 cities distributed all over the world. We used a dataset containing daily COVID-19 data for 167 cities from 01/05/2020 to 01/01/2022, along with variables related to atmospheric and environmental conditions. We found an expected positive relationship between increases in atmospheric NO 2 concentration and increases in the infective rate of COVID-19. We also found an unexpected negative relationship between PM10 and COVID-19 spread, which was stronger in unpolluted cities, and indicating a likely stronger and faster deactivation of the viruses by the absorption to the larger than to the smaller particles, to PM10 more than to PM2.5. Although a complete analysis would require taking into account the restrictions in the city and the immunization status of the population, and the variance of COVID-19 spread explained by PM10 was small, only up to approx. 2%, these results contribute to a better understanding of the impact of particles on the spread of COVID-19 and other respiratory viral diseases thus informing public health policies and interventions aimed at mitigating the impact of these pandemics.